Mapping pedagogical touchpoints: Exploring online student engagement and course design. (November 2022) - Tualaulelei, Eseta; Burke, Katie; Fanshawe, Melissa; Cameron, Cathy
Online learning has been widely adopted in higher education but there is a need to better understand the nature of student engagement with online courses. For example, there are questions about whether students engage with courses as educators intend and what features of online courses engage students to enhance learning. Bringing together student and educator perspectives, this article reports on a study that identified 'pedagogical touchpoints' – opportunities within online courses for student engagement – to ascertain whether a better understanding of these could improve online course design and student engagement. Data were collected across three undergraduate online courses. Data analysis produced three key findings: mapping pedagogical touchpoints against dimensions of engagement reveals patterns that may inform enhanced course design, students' engagement with pedagogical touchpoints varies according to their learning needs and desires, and mapping pedagogical touchpoints can inform course design at both conceptual and practical levels. Discussion of the findings highlights that purposeful design of online courses, including strategic planning for pedagogical touchpoints, can maximise the potential for student engagement and consequent learning.